2016
DOI: 10.4269/ajtmh.15-0840
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Detection of Antibodies to Eastern Equine Encephalitis, West Nile, St. Louis Encephalitis, and Turlock Viruses in Various Species of Wild Birds from Across the United States

Abstract: Abstract. Wild birds serve as amplifying hosts for many arboviruses, and are thought to be responsible for introducing these viruses into new areas during migration as well as reintroducing them to places where winter temperatures disrupt mosquito-borne transmission. To learn more about four mosquito-borne arboviruses of concern to human or animal health, we tested sera from 997 wild birds of 54 species and 17 families across 44 states of the United States collected from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…However, a more complete sampling of potential avian hosts is necessary to determine which species are participating in short-distance migration events responsible for SLEV genotype III movement between sites in this region. We suggest focusing efforts on species that were previously identified as seropositive ( Reisen and Wheeler, 2016 ), or those that have been identified through bloodmeal analyses, as previous studies have had relatively limited sample sizes for many species despite many decades of sampling for viral encephalitides ( Lord et al, 1974 ; Reisen et al, 2003 , 2005 ; Diaz et al, 2016 ; Pedersen et al, 2016 ; Díaz et al, 2018 ). Furthermore, the formation of monophyletic clades for 2017 and 2018 within Clade 2A, leads us to tentatively conclude that transient variants of SLEV are responsible for the seasonal circulation within Coachella Valley ( Reisen et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a more complete sampling of potential avian hosts is necessary to determine which species are participating in short-distance migration events responsible for SLEV genotype III movement between sites in this region. We suggest focusing efforts on species that were previously identified as seropositive ( Reisen and Wheeler, 2016 ), or those that have been identified through bloodmeal analyses, as previous studies have had relatively limited sample sizes for many species despite many decades of sampling for viral encephalitides ( Lord et al, 1974 ; Reisen et al, 2003 , 2005 ; Diaz et al, 2016 ; Pedersen et al, 2016 ; Díaz et al, 2018 ). Furthermore, the formation of monophyletic clades for 2017 and 2018 within Clade 2A, leads us to tentatively conclude that transient variants of SLEV are responsible for the seasonal circulation within Coachella Valley ( Reisen et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…Note that access in this study was defined as having slept under a net, or if not, having indicated that a space under a net was available, whereas in the reanalysis of the DHS data, access was defined as having slept under a net, or if not, if a space under a net was available, assuming two free spaces for an unused net and one space for a net that was already occupied by another person [10]. Intense study contact, in the form of fortnightly visits made by study personnel to participating intervention households, positively influenced net use: members of Group 3 (those not receiving either intervention or fortnightly visits) had lower net use than Groups 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…The trial was conducted in rural Greater Accra, an area with low (23.2%) net use despite 71% having access [10–12]. Of African countries surveyed with a demographic and health survey (DHS) in the 2012–2015 period, Ghana ranks near the bottom in net use, even among those reporting to have a net (57.5% use).…”
Section: Methodsmentioning
confidence: 99%
“…Additional broader studies that encompassed data on select species of Galliformes include: Japanese quail ( Coturnix japonica ; Komar et al 2003), guinea fowl ( Numida meleagris ; Blackmore et al 2003, Gibbs et al 2006), rock partridge ( Alectoris graeca ; Petrović et al 2013), common quail ( Coturnix coturnix ; Lan et al 2013), gray partridge ( Perdix perdix ; Pedersen et al 2016), common peafowl ( Pavo cristatus ; Komar et al 2001), pheasant (species not identified; Blackmore et al 2003, Brugman et al 2013), grouse (species not identified; Blackmore et al 2003), and partridge (species not identified; Brugman et al 2013). …”
Section: Methodsmentioning
confidence: 99%